Review on Fault Diagnosis Technology for High-speed EMU Gearboxes - Zhang Jianchao; Chen Xiangsong; Hao Rujiang; Gu Xiaohui; Ren Bin (Jixie chuandong)
The gearbox is an important component of the system of high-speed trains, which is susceptible to damage and failure due to the long-term high-speed and heavy-load working environment, so it is important to diagnose the faults of high-speed train gearboxes quickly and accurately. Thus, based on analysis of the structure type and common faults of the EMU gearbox, the current application status of the typical technologies such as vibration analysis, noise analysis, temperature field analysis, oil analysis and acoustic emission used for fault diagnosis of the EMU gearbox at home and abroad is explained, the applicability of these technologies is analyzed and key research directions are proposed. The analysis results show that the current multiple fault diagnosis technologies applied in high-speed EMU gearboxes have their own advantages, disadvantages and application occasions. The single diagnosis technology can not accurately diagnose the multi-type failures of the gearbox due to its limitations, and the fusion of multiple techniques based on advanced intelligent algorithms is expected to be one of the research focuses for fault diagnosis in this field in the future.